Celiac disease - Dina I Shehab (SpringerOpen, 2013)
Purpose of reviewThe aim of this review was to summarize recent advances in celiac disease (CD) published between 2006 and 2012. Recent findings CD affects ˜1% of most populations but remains largely unrecognized. During the past year, research has shown that the prevalence of CD has increased dramatically and not merely because of increased detection. Moreover, undiagnosed CD may be associated with increased mortality. Significant progress has been made in understanding how gliadin peptides can cross the intestinal border and access the immune system. New deamidated gliadin peptide antibodies have better diagnostic accuracy over other tests. The inclusion of duodenal bulb biopsy specimens may increase the rate of CD detection. Finally, refractory CD, although rare, is associated with a poor prognosis. The use of novel highly efficient exogenous prolyl endoproteases enzymes may help patients deal with occasional lapses in their diet or may protect highly sensitive individuals from inadvertent presence of gluten in food products. Nevertheless, the efficiency of this approach still needs precise assessment. Conclusion Mortality rates among patients with untreated CD increase two-fold every year as they age (gastrointestinal malignancies) and most can be prevented/reversed with early diagnosis and initiation of a gluten-free diet. CD is a global health problem that requires a multidisciplinary and increasingly cooperative multinational research effort.